Plant Species Classification and Diversity of the Understory Vegetation in Oak Forests of Swat, Pakistan - Ataur Rahman (11044485) (2021)
The forest ecosystem has understory vegetation that plays a vital role in sustaining diversity, providing nutrients, and forming a useful association for developing a balanced ecosystem. The current study provides detailed insights into the plant biodiversity and species classification of the understory vegetation of Swat, Pakistan. The floral diversity of the area was comprised of 58 plant species belonging to 32 families. The physiognomy of the studied area was dominated by herbaceous growth form with 47 species. The dominant life-form class was hemicryptophytes with 19 species (33%), followed by nanophanerophytes with 15 species (26%) and therophytes with 13 species (22%). Of the 58 species, 43 plant species were associated with group III clustered by applying Ward’s agglomerative clustering that indicated wide sociability of the species in the studied oak-dominated forests. Group III had higher species richness (10.3), α-diversity (2.74) and β-diversity (9.85), and Margalef index values (3.95). While the group I had maximum Pielous and Simpson index values of 0.97 and 7.13, respectively. Redundancy analysis revealed that seven variables (i.e., latitude, elevation, clay, wilting point, bulk density, saturation, and electric conductivity) were significantly influential concerning the understory vegetation of oak-dominated forests. The understory vegetation of these forests plays an important role in the forest ecosystem of the region. The present study reveals floral divergence and physiognomic scenario of the unexplored study area, which could be an important reference for future ethnobotanical, phytosociological, and conservational endeavors. Moreover, this information is important to the success of efforts intended to prevent the loss of species diversity in these forests by destroying their natural habitats. Other Information Published in: Applied Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/app112311372 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.